Validity and Reliability of Short-Form McGill Pain Questionnaire-2 (SF-MPQ-2) in Iranian People with Parkinson’s Disease - Maryam Mehdizadeh; Seyed-Mohammad Fereshtehnejad; Sepide Goudarzi; Ainaz Moshtagh; Farzaneh Dehghanian Nasrabadi; Sayed Amir Hasan Habibi; Ghorban Taghizadeh (Parkinson's Disease)
Purpose. Pain is one of the nonmotor symptoms of Parkinson’s disease (PD) that, in order to be better managed, requires to be evaluated. Evaluations are done using pain assessment scales such as the Short-Form McGill Pain Questionnaire-2 (SF-MPQ-2). The goal of this study was to assess the psychometric properties of SF-MPQ-2 to measure pain in people with PD. Methods. Four hundred and twenty-eight PD patients with a mean (SD) age of 60.11 (11.44) years were included. Accessibility was measured through floor and ceiling effects. Dimensionality was estimated by exploratory factor analysis. The association between SF-MPQ-2 and other scales such as Neuropathic Pain Symptom Inventory, Douleur Neuropathic 4, Brief Pain Inventory, King’s Pain Parkinson’s Disease Scale, and Visual Analog Scale-Pain was considered to calculate convergent validity. Internal consistency and test-retest reliability were assessed by Cronbach’s alpha and intraclass correlation coefficient (ICC), respectively. Results. A noticeable floor effect was found. Dimensionality results indicated four factors for this scale. A strong relationship was found between the SF-MPQ-2 total score and other scales (r = 0.55 to 0.85). In reliability analysis, Cronbach’s alpha and ICC were 0.93 and 0.94 for SF-MPQ-2, respectively. Conclusion. The results of this study showed that SF-MPQ-2 has adequate validity and reliability to measure pain in people with Parkinson’s disease.